Effects of functional characteristics of prickly ash leaves on yield following increased supply of nitrogen fertilizers - Liu, Junlan; Sun, Guoqing; Huang, Qin; Zhang, Haodan; Tian, Ailin; Liu, Linyu; Ren, Yun; Li, Qiang; Chen, Zexiong (Frontiers in Plant Science, 2026)
This study investigated the effects of nitrogen fertilizer on leaf morphology, photosynthetic pigments, photosynthetic characteristics, and yield of prickly ash (Zanthoxylum L.) and clarified the differences in the contribution of leaf morphology, photosynthetic pigments, and photosynthetic characteristics to this yield of prickly ash. Using Jiuyeqing as the experimental material, three nitrogen fertilizer levels of N0, N120, and N240 kg ha−1 were established. The results showed that nitrogen application improved the morphological and structural traits of prickly ash leaves, enhanced the contents of photosynthetic pigments and photosynthetic performance, significantly increased the accumulation of dry matter and nitrogen in plants, and notably elevated the ear number, 100-grain weight, single-ear weight, and yield. Correlation analysis found Leaf area, chlorophyll content, and net photosynthetic rate were highly positively correlated with yield. Leaf area contributed the most to yield, followed by the net photosynthetic rate, whereas chlorophyll content contributed the least. The results of path analysis showed that leaf area (0.422), chlorophyll content (0.237), and net photosynthetic rate (-0.098) exerted relatively small direct effects on the yield of prickly ash. Specifically, these three leaf traits, namely leaf area, chlorophyll content, and net photosynthetic rate, indirectly regulated the yield via nitrogen accumulation, with the corresponding indirect path coefficients being 1.656, 1.601, and 1.645, respectively. Therefore, nitrogen accumulation in prickly ash increased significantly after nitrogen application, which increased the photosynthetic leaf area, chlorophyll content, photosynthetic rate, and yield.